Antenatal Diagnosis of Marginal and Velamentous Placental Cord Insertion and Pregnancy Outcomes. Issue 4 (April 2020) - O'Quinn, Candace; Cooper, Stephanie; Tang, Selphee; Wood, Stephen
Abstract : OBJECTIVE: To evaluate the association between antenatal diagnosis of velamentous and marginal placental cord insertions with adverse perinatal outcomes of small-for-gestational-age (SGA) birth weight (less than the 5th percentile), caesarean birth, and perinatal mortality. METHODS: Using a diagnostic imaging database, we performed a cohort study of all consecutive singleton pregnancies (35, 391), including 1, 427 cases of marginal and 107 cases of velamentous cord insertion, delivered after 24 6/7 weeks of gestation between January 1, 2012, and December 31, 2015, at a single Canadian tertiary care center. Cases with placenta previa, vasa previa, no documented cord insertion, or fetal anomalies were excluded. RESULTS: In the overall cohort, the rate of birth weight less than the 5th percentile was 5.2%, the rate of cesarean delivery was 27.1%, and the rate of perinatal mortality was 0.24%. Velamentous cord insertion was associated with SGA (relative risk [RR] 2.19, 95% CI 1.28–3.74). This persisted after controlling for smoking during pregnancy, diabetes, and hypertension (adjusted odds ratio [aOR] 1.98, 95% CI 1.03–3.84). Velamentous cord insertion was also associated with an increased risk of caesarean birth (RR=1.38, 95% CI=1.08–1, 77) and perinatal death (1.87%, RR 8.15, 95% CI 2.02–32.8), a relationship that persisted after controlling for smoking during pregnancy, diabetes, and hypertension (aOR 1.53, 95% CI 1.01–2.32). Marginal cord insertion was not associated with birth weight less than the 5th percentile (RR 1.23, 95% CI 1.00–1.51), cesarean delivery (RR 1.01, 95% CI 0.92–1.10), or perinatal death (RR 1.53, 95% CI 0.62–3.78). CONCLUSION: Antenatal diagnosis of velamentous placental cord insertion is associated with birth weight less than the 5th percentile. Abstract : Velamentous placental cord insertion was associated with birth weight less than the 5th percentile.